COLORED REVOLUTIONS": let’s overthrow the government, #allegriaalegria, from the "shadows" (no violence!) we strike democracy - Fernandes, Roberto Mauro da Silva (Seven Editora, 2023)
Beginning in the 2000s a series of mass demonstrations were recorded Eastern Europe, Central Asia, North Africa, and Latin America, these movements were credited with the changes in government that occurred in these regions. These large protests became known as the "color revolution. According to the mainstream press these actions were led by different social segments that were dissatisfied with their governments, as well as protesting against dictatorships. However, there are indications that the "color revolutions" are geopolitical tools that make use of the democratic system to change governments. Therefore, the purpose of this discussion is to reflect on aspects of the infrastructure that enables "color revolutions" to be prepared and then executed. We will demonstrate how some actors move on the "surface" and in the "shadows" of the international network that operates the "color revolutions". To do so, we conducted a literature search, as well as, theoretically support the theory of Hybrid Warfare. DOI: https://doi.org/10.56238/methofocusinterv1-116